Precision Nutrition and Advanced Culinary Medicine - Police, Sara B. (Open textbook library., 2023)
This electronic textbook (eBook) and/or eBook chapters are designed to accompany NS801, Precision Nutrition and Advanced Culinary Medicine, a 1-credit, 8-week online medical elective course for the University of Kentucky College of Medicine Office of Medical Education curricula. Reading for the course will be labeled to align with the content of the online course; such that Module 2 is aligned with Chapter 2, Module 3 with Chapter 3, and so on. As an open access textbook supported by the University of Kentucky Libraries Alternative Textbook program, all sources will be linked and readily available.